2016
DOI: 10.1186/s13006-017-0100-6
|View full text |Cite
|
Sign up to set email alerts
|

Maternal work and exclusive breastfeeding practice: a community based cross-sectional study in Efutu Municipal, Ghana

Abstract: BackgroundMaternal work has been identified as one of the factors that affect exclusive breastfeeding in the first six months of life. In Ghana, mothers engaged in the formal sector of employment are unable to exclusively breastfeed after maternity leave because facilities at their work places and conditions of work do not support exclusive breastfeeding. Even though maternal work and exclusive breastfeeding does not seem well matched, not all maternal work are incompatible with the practice of exclusive breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 16 publications
(14 reference statements)
2
59
2
2
Order By: Relevance
“…This finding also contradicted a similar study with a similar methodology conducted by Atchiri and Dako (2017) that higher coverage of proper IYCF practice were associated with maternal age (Atchibri & Dako, 2017). A study conducted by Tan (2011) reported that younger age mothers tend not to exclusively breastfeed and this may be because they are more likely to engage in activities that make it difficult for them to breastfeed of which includes education and employment (Nkrumah, 2017) but this study shows no association of that sort. This could be as a result of different methodological approaches that has been used.…”
Section: Discussioncontrasting
confidence: 56%
“…This finding also contradicted a similar study with a similar methodology conducted by Atchiri and Dako (2017) that higher coverage of proper IYCF practice were associated with maternal age (Atchibri & Dako, 2017). A study conducted by Tan (2011) reported that younger age mothers tend not to exclusively breastfeed and this may be because they are more likely to engage in activities that make it difficult for them to breastfeed of which includes education and employment (Nkrumah, 2017) but this study shows no association of that sort. This could be as a result of different methodological approaches that has been used.…”
Section: Discussioncontrasting
confidence: 56%
“…Increased stress can impair lactogenesis and may lower oxytocin, thereby limiting milk letdown and output (Dewey, 2001;Stuebe, Grewen, & Meltzer-Brody, 2013). Further, food insecurity may compel mothers to seek employment outside the household or work for a greater proportion of the day, thereby disrupting normal feeding patterns and limiting the frequency and duration of feeding (Abou-ElWafa & El-Gilany, 2018;Nkrumah, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These barriers will be discussed. Findings of many research studies stated that maternal employment and early return to work or school were factors associated with shorter duration of continue exclusive breastfeeding 6,4,12,11,5,8 .More mothers in the informal sector of employment exclusively breastfeeding their infants and breastfeeding more than eight times compared to mothers in formal sectors of employment, Family support, bed-shearing, flexible work schedule and cultural beliefs are key factors of exclusive breastfeeding and breastfeeding frequency 5 . Mothers who are returning to work or school need for encouraging and to establish policies that allow flexibility at work and appropriate places to breastfeeding or expressmilk 11 .…”
Section: Low Social Supportmentioning
confidence: 99%
“…In this section, discussion of the reviewed studies will focus on reported reliability and validity of the instrument. Reliability concerns a measure's accuracy and for the purpose of this review related measuring perceived socio-demographic characteristics and social support internal consistency, Cronbach's alpha and interclass confident ).Stability of instrument over period of time (testretest).Only one study included this review assessed internal consistency reliability of following scales; Likert scale and self-efficiency designed by Dennis (2003) is questionnaire a 33-item and is scored by a 5-point Likert scale from always confident 5 to not at all confident 1 . Scores range from 33-165, with 33-76 considered low self-efficacy, 77-120 average self-efficacy, and 121-165 regarded as high self-efficacy 3 .…”
Section: Reliabilitymentioning
confidence: 99%
See 1 more Smart Citation